2015
DOI: 10.1088/0957-4484/26/36/365104
|View full text |Cite
|
Sign up to set email alerts
|

Poly(D,L-lactide-co-glycolide) nanoparticles as delivery agents for photodynamic therapy: enhancing singlet oxygen release and photototoxicity by surface PEG coating

Abstract: Poly(D, L-lactide-co-glycolide) (PLGA) nanoparticles (NPs) are being considered as nanodelivery systems for photodynamic therapy. The physico-chemical and biological aspects of their use remain largely unknown. Herein we report the results of a study of PLGA NPs for the delivery of the model hydrophobic photosensitizer ZnTPP to HeLa cells. ZnTPP was encapsulated in PLGA with high efficiency and the NPs showed negative zeta potentials and diameters close to 110 nm. Poly(ethylene glycol) (PEG) coating, introduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…For in vitro release experiments, PBS is a commonly used release medium to maintain constant pH and osmolarity that match with body fluids. To further imitate in vivo situation in blood, however, testing in serum (i.e., plasma from which the clotting proteins have been removed) or plasma‐contained media is more suitable because they include the effects of plasma/serum proteins and different ionic species in tissue fluids . Generally, it was found that the drug release and degradation rates are faster in serum and plasma than in PBS.…”
Section: Physiological Factors (Testing Environments)mentioning
confidence: 99%
“…For in vitro release experiments, PBS is a commonly used release medium to maintain constant pH and osmolarity that match with body fluids. To further imitate in vivo situation in blood, however, testing in serum (i.e., plasma from which the clotting proteins have been removed) or plasma‐contained media is more suitable because they include the effects of plasma/serum proteins and different ionic species in tissue fluids . Generally, it was found that the drug release and degradation rates are faster in serum and plasma than in PBS.…”
Section: Physiological Factors (Testing Environments)mentioning
confidence: 99%
“…Furthermore, when the carriers were added to the culture medium no turbidities appear that could indicate the formation of aggregates. 63 Fluorescence spectroscopy was used to conrm the presence of the two synthesized porphyrins ATPP-LA and ZnATPP-LA on the GNP surface thanks to the ability of the porphyrins to emit uorescence. 64 The uorescence emission spectra were recorded for the free porphyrins (ATPP-LA and ZnATPP-LA) in CHCl 3 solution and for the porphyrin-coated GNP in aqueous solution (see ESI Fig.…”
Section: Synthesis and Characterization Of Porphyrin-functionalized Gmentioning
confidence: 99%
“…In vitro phototoxicity investigations evidenced that the novel nanocarrier ZnTriMPyP‐PLGA‐PLA‐PEG‐c(RGDfK) is effective at nanomolar concentrations of PS and devoid of dark toxicity. This is a major improvement compared to our previous nanosystems in which the related PS zinc(II) tetraphenyl porphyrin (ZnTPP) was occluded in PLGA‐PEG NPs, which required longer incubation periods (24 h vs 2 h) and 10‐fold higher PS concentrations to reach similar endpoints, albeit at lower light fluences (27). Similar results were obtained using a closely related nanosystem, PLA‐PEG‐c(RGDfK) NPs with an occluded PS, pyropheophorbide a (PPa), which also required a 10‐fold higher concentration to achieve a comparable phototoxicity (see Supporting Information).…”
Section: Resultsmentioning
confidence: 92%
“…In the same way, previous research in our group demonstrated that 10% PEG coating confers high stability to PLGA NPs in the presence of serum proteins. In contrast, when 5% of PEG is used, PLGA NPs aggregate and precipitate, while increasing the PEG content to 15% leads to highly heterogeneous NP populations (27). For this reason, in the present study, 10% PEG was kept constant in all the prepared nanocarriers.…”
Section: Resultsmentioning
confidence: 99%